Wide-field broad-band radio imaging with phased array feeds: A pilot multi-epoch continuum survey with ASKAP-BETA - Heywood, I.; Bannister, K.; Marvil, J.; Allison, J.; Ball, L.; Bell, M.; Bock, D.; Brothers, M.; Bunton, J.; Chippendale, A.; Cooray, F.; Cornwell, T.; et al. (Oxford University Press, 2016)
The Boolardy Engineering TestArray is a 6×12mdish interferometer and the prototype of the Australian Square Kilometre Array Pathfinder (ASKAP), equipped with the first generation of ASKAP's phased array feed (PAF) receivers. These facilitate rapid wide-area imaging via the deployment of simultaneous multiple beams within an ~30 deg2 field of view. By cycling the array through 12 interleaved pointing positions and using nine digitally formed beams, we effectively mimic a traditional 1 h × 108 pointing survey, covering ~150 deg2 over 711-1015 MHz in 12 h of observing time. Three such observations were executed over the course of a week. We verify the full bandwidth continuum imaging performance and stability of the system via self-consistency checks and comparisons to existing radio data. The combined three epoch image has arcminute resolution and a 1s thermal noise level of 375 µJy beam-1, although the effective noise is a factor of ~3 higher due to residual sidelobe confusion. From this we derive a catalogue of 3722 discrete radio components, using the 35 per cent fractional bandwidth to measure in-band spectral indices for 1037 of them. A search for transient events reveals one significantly variable source within the survey area. The survey covers approximately two-thirds of the Spitzer South Pole Telescope Deep Field. This pilot project demonstrates the viability and potential of using PAFs to rapidly and accurately survey the sky at radio wavelengths.